Gastroenterology Fellowship Training: Approaches to Curriculum Assessment and Evaluation. (2008) - Raman, Maitreyi; Shaffer, Eldon; Lockyear, Jocelyn
Abstract : BACKGROUND: Medical education requires ongoing curriculum development and evaluation to incorporate new knowledge and competencies. The Kern model of curricular development is a generic model to guide curriculum design, whereas the Royal College of Physicians and Surgeons of Canada (RCPSC) has a specific model for curriculum development through its accreditation structure. OBJECTIVE: To apply the Kern model to an assessment of a residency program in gastroenterology. METHODS: A case study was used, which is a method of qualitative research designed to help researchers understand people and the societal contexts in which they live. RESULTS: The six steps involved in the Kern model of curricular development include problem identification; needs assessment; establishing objectives; establishing educational strategies; implementation; and evaluation. The steps of the RCPSC model of curriculum development include establishing an administrative structure for the program; objectives; structure and organization of the program; resources; clinical, academic and scholarly content of the program; and evaluation. Two differences between the models for curriculum development include the ability of the Kern model to conduct problem identification and learner needs assessment. Identifying problems that exist suggests a need for an educational program, such as the long wait times for gastroenterology referrals. Assessing learner needs allows for the development of a tailored curriculum for the trainee. CONCLUSIONS: The Kern model and RCPSC model for curriculum development are complementary. Consideration by the RCPSC should be provided to add the missing elements of curriculum design to the accreditation structure for completeness.